Students Critical Thinking Skills Through Project-Based Learning Models in Solving Pythagoras Theorem Problems - Liliyani Sameth; Djaffar Lessy (Lembaga Intelektual Muda (LIM) Maluku, 2022)
Mathematics is a symbolic language of its characteristics is to use deductive reasoning and inductive reasoning methods. In the teaching of mathematics each subject is a unit so that the mastery of one subject is a support to learn the next subject. Similarly, the ability of students in carrying out calculating operations in mathematics lessons in developing students' critical thinking skills. To perform calculating operations on the right learning requires the right learning model and teaching materials. Therefore, the right learning model in cultivating students' critical thinking skills is a project-based learning model. This research aims to find out the ability to think critically through project-based learning models on the material of the theorem theorem phytagoras of students in class VIII of State Junior High School 5 West Leihitu District. The type of research used in this study is qualitative descriptive. The process of taking subjects is based on the highest value of group work on LKS. From the results of the group's work, 3 students were taken from the total number of students, namely 30 people. The instruments used in this study were researchers, tests and interviews. The data analysis techniques used follow concepts developed by Miles and Huberman, namely data reduction, data presentation, and inference. The results of the data analysis obtained that the critical thinking skills possessed by each student vary. From the results of interviews with 3 subjects, it is known that sl subjects meet 4 indicators of critical thinking skills used in this study, namely providing simple explanations, building basic abilities, making conclusions, and providing advanced explanations. The AH subject meets two indicators: providing simple explanations and building basic skills. While the subject of RK only met one indicator used in this study, namely building basic capabilities in the problem-solving process.